“Diseño de un sistema de planificación y control en la fábrica Induce del Ecuador para la gestión eficiente de la producción”. - Fajardo Pinto, Jordy Leonardo (2021)
This research is focused on different problems that have arisen at present within the Induce Factory of Ecuador and its production processes, the main one being the lack of a planning system that produces an inefficient management in production. The main objective is the development of a planning and control system based on the study of times and movements elaborated with the container manufacturing activities, calculating the current productivity indexes, this information will be reflected in an automated spreadsheet, in this way an efficient production management will be achieved. To achieve these objectives, we will apply a descriptive type of research since the information is based on existing data of the company, the inductive method will allow us to achieve general results from particular premises, relying on the development of diagrams, layout, time analysis and redistribution of the plant. The proposed improvement system shows that the level of efficiency has increased from 86.17% to 96.81%, thus reducing unproductive times to 3.79% without the need to increase the available capacity of the plant. Finally, the veracity of the data obtained from the system is verified by means of a simulation carried out in the ProModel platform, demonstrating that the proposed production planning and control system is effective.